Visual Brand Architecture WB Kitchen - Dzaky Assrof; San Ahdi (Jurnal Riset Rumpun Seni, Desain dan Media, 2024)
WB Kitchen is a culinary business located in Batusangkar, West Sumatra. WB Kitchen has 3 subsidiaries, namely WB Cake, WB Rendang, and WB Catering.WB itself is taken from the initials of Mrs. Rahmiwati Bur's nickname, namely "Wati Bur" as the owner. WB kitchen and other subsidiaries still do not have an optimal logo or visual identity, making it difficult to be remembered and recognized by the target audience. This design uses the Design Thinking method with an approach through empathy as the first step, then supported by the SWOT analysis method, namely, Strenght, Weakness, Opportunity and threath. The design of visual brand architecture is done to optimize and give characteristics to WB Kitchen. Therefore, a visual identity guid line book was made as the main media and supported by other supporting media such as Greeting Cards, Aprons, Posters, Chef Shirts, Polo Shirts, Cake Packaging and so on.